Dexamethasone-induced insulin resistance is associated with increased connexin 36 mRNA and protein expression in pancreatic rat islets - Rafacho, A.; Roma, L. P.; Taboga, S. R.; Boschero, A. C.; Bosqueiro, José Roberto [UNESP] (Natl Research Council Canada-n R C Research Press, 2007)
Augmented glucose-stimulated insulin secretion (GSIS) is an adaptive mechanism exhibited by pancreatic islets from insulin-resistant animal models. Gap junction proteins have been proposed to contribute to islet function. As such, we investigated the expression of connexin 36 (Cx36), connexin 43 (Cx43), and the glucose transporter Glut2 at mRNA and protein levels in pancreatic islets of dexamethasone (DEX)-induced insulin-resistant rats. Study rats received daily injections of DEX (1 mg/kg body mass, i.p.) for 5 days, whereas control rats (CTL) received saline solution. DEX rats exhibited peripheral insulin resistance, as indicated by the significant postabsorptive insulin levels and by the constant rate for glucose disappearance (K-ITT). GSIS was significantly higher in DEX islets (1.8-fold in 16.7 mmol/L glucose vs. CTL, p < 0.05). A significant increase of 2.25-fold in islet area was observed in DEX vs. CTL islets (p < 0.05). Cx36 mRNA expression was significantly augmented, Cx43 diminished, and Glut2 mRNA was unaltered in islets of DEX vs. CTL (p < 0.05). Cx36 protein expression was 1.6-fold higher than that of CTL islets (p < 0.05). Glut2 protein expression was unaltered and Cx43 was not detected at the protein level. We conclude that DEX-induced insulin resistance is accompanied by increased GSIS and this may be associated with increase of Cx36 protein expression.
Keywords: connexins; glucocorticoids; insulin resistance; glucose-stimulated insulin secretion; pancreatic islets